Stilling the Storm : Contemporary Responses to Mark 4.35-5.1 - Vincent, John (Practice Interpretation, 2011)
Most books about Jesus and the Gospels deal with texts, background, culture and authorial intentions. A new approach to the Gospels called Practice Interpretation puts the emphasis on the actual happenings behind the Gospel stories - on what first hearers might have made of them, and on what contemporary disciples today make of them. The concern of the studies in this series is with the "use" of a Gospel story by disciples today, and of its "influence" on them. In this ground-breaking collection, the first in the Practice Interpretation series, people from many different situations describe what the story of Jesus Stilling the Storm actually "sparked off" in their lives.